Does telecommunications reinforce rural agricultural extension services: Insights from tribal villages in Eastern India - Pradyot Ranjan Jena; Raja Rajendra Timilsina; Rajesh Kalli; Dil Bahadur Rahut; Tetsushi Sonobe (Asian Development Bank Institute (ADBI), 2024)
Conventional agricultural extension services in rural India have been insufficient due to various constraints, including accessibility, finances, and lack of access to other resources. These services primarily depend on in-person visits and physical demonstrations of farming practices, making them only feasible for some farmers. The increasing use of digital and telecommunications technology in rural areas has created an opportunity to improve extension services. This study examines how telecommunications support extension services impact crop productivity among farmers in tribal communities in Odisha, India. The study used a data envelopment analysis (DEA) model to measure the productive efficiency of 513 paddy cultivators in Odisha. Additionally, an endogenous switching regression model was employed to assess the impact of telecommunication-based extension services on technical efficiency scores while controlling for other variables. The study also considered the probability of telecommunication-based extension services influencing the adoption of climate-smart agricultural practices (CSA). The results show that over 80% of paddy cultivators in the region exhibited low farming efficiency. The overall technical efficiency of these cultivators ranged from 0.02 to 1, with an average efficiency score of 0.14. The empirical findings revealed mixed effects of telecommunication-based extension services on paddy cultivation. The telecommunication-based extension services did not unequivocally improve farm productivity, but did positively influence farmers' adoption of Climate-Smart Agriculture (CSA) practices. Given the low levels of education and technical understanding among farmers in the study area, telecommunication-based extension has yet to lead to greater farm efficiency. However, telecommunication-based extension has significant potential to complement physical extension services. Although farmers currently prefer physical extension due to its two-way communication and familiarity, the government can make telecommunication-based extension more user-friendly through better planning and design. There is a need for policy action to develop targeted digital infrastructure to meet farmers' needs effectively.
Keywords: Q12; Q55; O33; L86; 330; digital extension; data envelopment analysis; endogenous switching regression; climate-smart agriculture